PENAMBAHAN RIMPANG KUNYIT (CURCUMA DOMESTICA VAL.), TEMULAWAK (CURCUMA XANTHORRHIZA ROXB.), DAN TEMU PUTIH (CURCUMA ZEDOARIA ROSC.) DALAM RANSUM KOMERSIL TERHADAP KUALITAS TELUR BURUNG PUYUH (Coturnix-coturnix japonica) - Rondonuwu, Claudia; Saerang, J L.P; Nangoy, F J; Laatung, S (ZOOTEC, 2014)
ABSTRACTADDITION TURMERIC GINGER, RHIZOME AND WHITE RHIZOME OF COMMERCIAL RATION TO EGGS’ QUALITY OF QUAILS.This study aims to determine the quality of quail eggs after added 2% turmeric (Curcuma domestica Val.), ginger (Curcuma xanthorrhiza Roxb.), and ginger and white (Curcuma zedoaria Rosc.) in the commercial ration. Animals used are of the type Coturnix-coturnix japonica quail females aged 6 weeks a total of 120 birds. Research using completely randomized design (CRD) with 4 treatments and 5 replications, and each replication consisted of 6 tail quail. Treatment is given as follows: R0 = control diet; R1= ration with 2% turmeric (Curcuma domestica Val.), R2 = 2% ration with ginger (Curcuma xanthorrhiza Roxb.), R3 = 2% ration with ginger and white (Curcuma zedoaria Rosc.). results of the study showed that the addition of 2% turmeric (Curcuma domestica Val.), ginger (Curcuma xanthorrhiza Roxb.), ginger and white (Curcuma zedoaria Rosc.) and not significantly different effect on egg weight, yolk color and egg shell thickness. And based on the results of this study concluded that the addition of 2% turmeric, ginger, ginger and white and can not increase egg weight, yolkcolor and egg shell thickness when added to a commercial ration.Keyword : Ration, Turmeric, Ginger, Ginger and White, Quail Eggs.